Controllable TiO2 heterostructure with carbon hybrid materials for enhanced photoelectrochemical performance. (11th April 2017) - Ge, Yilin; Bai, Hongye; Li, Chunfa; Guan, Peng; Wu, Linlan; Xu, Dongbo; Hong, Yuanzhi; Fan, Weiqiang; Shi, Weidong
Abstract : A TiO2 /RGO/C3 N4 heterostructure has been successfully designed and fabricated, and the narrow bandgap and conductivity of RGO and C3 N4 could be beneficial for the generation and separation of photocharges. Abstract : In TiO2 both advantages (stability and low cost) and disadvantages (large bandgap) coexist, so how to optimize a bare TiO2 electrode is a continuous hot topic for the construction of suitable photoelectrochemical (PEC) devices based on TiO2 for water splitting. This paper reports a facile and simple fabrication of a TiO2 /RGO/C3 N4 photoelectrode for PEC splitting of water. Its heterostructure configuration has been characterized and confirmed by XRD, Raman spectroscopy, XPS, TEM and STEM. The introduction of both RGO and C3 N4 film onto the surface of TiO2 is mainly due to the fact that C3 N4 has a strong photoelectric ability to respond to visible light and RGO plays an important role in the fast transfer of photogenerated charges across interfaces. Photocurrent and monochromatic incident photon-to-photocurrent efficiency (IPCE) of the titled heterostructure have been obviously improved, and the IPCE value (0.5 V vs. AgCl/Ag) of TiO2 /RGO/C3 N4 was estimated to be up to 28% at a wavelength of 400 nm.